1991
DOI: 10.3379/jmsjmag.15.s2_1019
|View full text |Cite
|
Sign up to set email alerts
|

CoCrTa/CoZrNb PERPENDICULAR MAGNETIC HARD DISK

Abstract: Low noise perpendicular magnetic recording hard disk using an amorphous soft magnetic CoZrNb underlayer, has been developed. Soft magnetic layer is prepared by the depositing materials on the disk substrates in the magnetic field directed radially by the magnets in a DC magnetron sputtering system. CoZrNb underlayer with magnetic easy axis uniform in the radial direction is more easily producible than a permalloy underlayer on the glass substrate. Perpendicular recording layer with high crystal orientation (A8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The PMR media used in commercial HDDs employ the double magnetic layer structure consisting of a semi-hard magnetic recording layer stacked on a soft magnetic underlayer, which is the basic PMR structure proposed by Prof. Iwasaki 1) . Until late 1990's, the Co-alloy recording layer was deposited directly on a thick softmagnetic underlayer of crystalline Fe-Ni 94,95) , amorphous Co-Zr-Nb 11,96) , etc. However, a series of research has shown that the medium noise can be reduced by introducing a thin nonmagnetic layer between the soft magnetic underlayer and the semi-hard recording layer, where the nonmagnetic layer is now defined as an intermediate layer since the soft magnetic layer is called as "underlayer" in the double layer structure 97) .…”
Section: Introductionmentioning
confidence: 99%
“…The PMR media used in commercial HDDs employ the double magnetic layer structure consisting of a semi-hard magnetic recording layer stacked on a soft magnetic underlayer, which is the basic PMR structure proposed by Prof. Iwasaki 1) . Until late 1990's, the Co-alloy recording layer was deposited directly on a thick softmagnetic underlayer of crystalline Fe-Ni 94,95) , amorphous Co-Zr-Nb 11,96) , etc. However, a series of research has shown that the medium noise can be reduced by introducing a thin nonmagnetic layer between the soft magnetic underlayer and the semi-hard recording layer, where the nonmagnetic layer is now defined as an intermediate layer since the soft magnetic layer is called as "underlayer" in the double layer structure 97) .…”
Section: Introductionmentioning
confidence: 99%